Comparison of Measurements Methods Intended to Determination of the Shrinkage Development in Polymer Cement Mortars. (2017) - Kucharczyková, Barbara; Karel, Ondřej; Daněk, Petr; Kocáb, Dalibor; Pőssl, Petr
Abstract: The paper deals with the experimental determination of the shrinkage progress of the polymer cement (PCC) mortars. The main motivation of performed measurements was to compare the results obtained from two different measurement procedures based on the measurement of the relative length changes and relative mass losses of the test specimens during whole time of ageing. Performed experimental analysis, focused on the determination of the progress of the relative length changes and relative mass losses, showed advantages and disadvantages of investigated measurement procedures. All performed measurements exhibited almost the same total progress of relative mass losses regardless of the used test procedure and size of specimens. The differences in the relative length changes originated from the capabilities, limitations and regulations of particular measurement procedures.